Extraordinary popular delusions and the madness of crowds - Mackay, Charles (Boston Page & company, 1932)
The text concentrates on a wide variety of phenomena which had occurred over the centuries prior to this book's publication in 1841. Mackay begins by examining various economic bubbles, such as the infamous Tulipomania - wherein Dutch tulips rocketed in value amid claims they could be substituted for actual currency - and various follies spread by word of mouth in urban areas.
Keywords: Impostors and imposture